2001
DOI: 10.1074/jbc.m108313200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation Is Involved in the Activation of Metal-regulatory Transcription Factor 1 in Response to Metal Ions

Abstract: We have studied the role of phosphorylation in the activation of metal-regulatory transcription factor-1 (MTF-1) and metallothionein (MT) gene expression. We showed that MTF-1 is phosphorylated in vivo and that zinc stimulates MTF-1 phosphorylation 2-4-fold. Several kinase inhibitors were used to examine the possible involvement of kinase cascades in the activation of MTF-1. Metal-induced MT gene expression was abrogated by protein kinase C (PKC), c-Jun N-terminal kinase (JNK), phosphoinositide 3-kinase, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
97
2
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(108 citation statements)
references
References 64 publications
7
97
2
2
Order By: Relevance
“…9). This is consistent with reports that Zn 2ϩ can activate gene expression by a PI3K-and JNK-dependent process (30). Alternatively, elevated metal levels could promote release of growth factors or other ligands that, in turn, activate PI3K, MAPK, and additional pathways.…”
Section: Discussionsupporting
confidence: 78%
“…9). This is consistent with reports that Zn 2ϩ can activate gene expression by a PI3K-and JNK-dependent process (30). Alternatively, elevated metal levels could promote release of growth factors or other ligands that, in turn, activate PI3K, MAPK, and additional pathways.…”
Section: Discussionsupporting
confidence: 78%
“…Nuclear MTF-1 binds to specific DNA sequences termed as metal response elements (MREs) and in turn activates MT transcription (22,24). It has been reported that MTF-1 activation requires stress-induced posttranslational modifications including phosphorylation (25). Although previous study demonstrates that the dephosphorylation of MTF-1 leads to its activation (24), the dynamic regulatory pattern remains unknown.…”
Section: Discussionmentioning
confidence: 86%
“…Previous reports have indicated that MTF-1 activity is mainly regulated by phosphorylation (24,25). Although protein kinases such as protein kinase C (PKC), c-Jun N-terminal kinase (JNK), or phosphoinositide 3-kinase (PI3K) have been reported to be involved in modifying the MTF-1 signaling pathway (24,25), the dynamic changes of phosphorylated MTF-1 in transactivation of MT remains to be defined. Because specific dephosphorylation of this transcription factor contributes to its activation (24), it is crucial to identify the specific protein phosphatases involved in transcriptional activation of MTF-1 under heavy metal stress.…”
Section: Induction Of Metallothionein (Mt) Expression Is Involved In mentioning
confidence: 99%
See 1 more Smart Citation
“…Other inducers, such as glucocorticoids and alkylating agents, may also interact with MTF1-associated proteins to activate MTF1, because these inducers are unlikely to interact with the zinc fingers directly. Phosphorylation of MTF1 was observed and may contribute to nuclear translocation of activated MTF1 (33)(34)(35). Arsenic (As 3ϩ ) is a human carcinogen and a pleiotropic toxic metalloid that causes cancer (particularly of the skin, lung, bladder, and liver), neuropathy, cardiovascular lesions, ovarian dysfunction, aberrant embryonic development, and postnatal growth retardation in humans (36 -42).…”
mentioning
confidence: 99%